Adaptive increases in liver cocaine n-demethylation induced by the drug in rats receiving different levels of utilizable protein. II. Evidences of new enzymatic protein synthesis and adrenal gland participation - Puma, Guillermo (1981)
Adaptive increases in liver cocaine n-demethylation induced by the drug in rats receiving different levels of utilizable protein. II. Evidences of new enzymatic protein synthesis and adrenal gland participation